2014
DOI: 10.1177/1524839914541277
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Implementation of Diabetes Self-Management

Abstract: To enhance the health and well-being of patients managing type 2 diabetes, the five grantees comprising the Alliance to Reduce Disparities in Diabetes implemented evidence-based approaches to patient self-management education as part of their programs. This article describes strategies implemented by the grantees that may help explain program success, defined as improvement in clinical values and patient-reported outcomes. A process evaluation of grantee programs included interviews and document review at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 19 publications
2
17
1
Order By: Relevance
“…Management of diabetes among older adults is complicated and includes issues related to cognitive and functional decline, and diabetes management in this population may have different aims than in younger populations. A study by Lewis and colleagues found that care management enhanced patient empowerment and addressed local barriers and individual needs with coordination of resources from a variety of settings [ 7 ], whereas the present results indicated that coordination of multiple programs addressing diabetes and its complications may hinder accessing the benefits of care management due to complex systems. Another qualitative study focusing on care coordination for insulin initiation in patients with diabetes explored different clinician perceptions of roles as they pertained to developing relationships with clear communication, trust, and respect [ 18 ].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Management of diabetes among older adults is complicated and includes issues related to cognitive and functional decline, and diabetes management in this population may have different aims than in younger populations. A study by Lewis and colleagues found that care management enhanced patient empowerment and addressed local barriers and individual needs with coordination of resources from a variety of settings [ 7 ], whereas the present results indicated that coordination of multiple programs addressing diabetes and its complications may hinder accessing the benefits of care management due to complex systems. Another qualitative study focusing on care coordination for insulin initiation in patients with diabetes explored different clinician perceptions of roles as they pertained to developing relationships with clear communication, trust, and respect [ 18 ].…”
Section: Discussioncontrasting
confidence: 55%
“…Complications are largely preventable with medication and behavioral interventions [ 4 , 5 ]. However, the disease remains prevalent in the US and globally, leaving health care services at the system and population levels challenged to deliver sustainable and effective interventions to decrease associated mortality and morbidity [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…We conducted and analyzed data from 97 interviews among 65 participants; some of the same individuals were interviewed in more than one site visit (see Table 1; Lewis, Williams, et al, 2014). See Lewis, Williams, et al (2014) for a detailed description of our data collection procedures. This research was reviewed and approved by the RTI International institutional review board.…”
Section: > > Methodsmentioning
confidence: 99%
“…Framework analysis provides a systematic, five-stage approach to organizing and analyzing qualitative data. Table 2 summarizes these five stages and their application to this evaluation (Lewis, Williams, et al, 2014). …”
Section: > > Methodsmentioning
confidence: 99%
“…The demographic variables for all program participants are reported elsewhere (see Table 3 of Lewis et al, 2014). The 1,827 program participants with baseline and follow-up data included African Americans (37%), Hispanics (48%), Native Americans (5%), Asians/Pacific Islanders (1%), and other/mixed race (1%).…”
Section: Resultsmentioning
confidence: 99%